Data Vocalization Enhancing Voice Output of Relational Data Base - Afaf Khaleel Edinat, Fatima Omar Haimour, Duha ‘Moh’d Basam’ Qutishat, (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
Recent advances in automatic speech recognition and natural language processing have led to a new generation of robust voice-based interfaces. Yet, there is very little work on using voice-based interfaces to query database systems. Current trends towards voice-based interfaces motivate the problem of data vocalization, a complementary problem to data visualization. So, the research on data visualization aims at finding the best way to present data via visual interfaces. In this paper we will discuss method to classify the users and their interest of how to select between the simple voice outputs row by row and concise version to find the good policies to select between simple and concise version is an interesting direction. This work is considered as extend to work proposed by Trummer et al.[1].
Keywords: Data Vocalization, Relational Data Base, Speaking Time Customization